Conditional strong matching preclusion of the pancake graph. Issue 1 (2nd January 2023) - Abdallah, Mohamad; Cheng, Eddie
ABSTRACT: The strong matching preclusion number of a graph is the minimum number of vertices and edges whose deletion results in a graph that has neither perfect matchings nor almost-perfect matchings. Park and Ihm introduced the problem of strong matching preclusion under the condition that no isolated vertex is created as a result of faults. In this article, we find the conditional strong matching preclusion number for the pancake graph.